Efektivitas Proses Rekrutmen Pegawai Negeri Sipil di Sekretariat Pendidikan Wilayah Administratif Khusus Oekusi Ambeno – Timor Leste - Sipa, Hermenegildo; Dwimawanti, Ida Hayu; Herawati, Augustin Rina; Afrizal, Teuku (Mahesa Research Center, 2021)
This research focuses on the process of recruitment of civil servants, referring to the effectiveness that must be carried out properly, provide useful results and achieve goals. Secretariat of Education, Special Administrative Region of Oecusi, Timor Leste conducts recruitment to find, find applicants and produce civil servants who have the quality, ability, competence and knowledge as needed. In examining the effectiveness of the recruitment process, qualitative research types are used which are defined in various ways according to the viewpoints used by experts. There are three findings found in this study, namely a) violations of administrative requirements, b) the recruitment process is ineffective and does not meet recruitment standards, and c) there is compromise and political intervention. Closing the results of the research, this article in addition to providing informative contributions but also as a reference material in conducting or improving an effective recruitment process in the future.